Targeting the STAT3/IL-36G signaling pathway can be a promising approach to treat rosacea - Xin Meng; Yun Zhong; Xuyuan Kuang; Yiya Zhang; Li Yang; Yisheng Cai; Fan Wang; Fanping He; Hongfu Xie; Ben Wang; Ji Li (Journal of Advanced Research)
Background: Rosacea is an inflammatory skin disorder characterized by the release of inflammatory mediators from keratinocytes, which are thought to play a crucial role in its pathogenesis. Despite an incidence of approximately 5.5%, rosacea is associated with a poor quality of life. However, as the pathogenesis of rosacea remains enigmatic, treatment options are limited. Objectives: To investigate the pathogenesis of rosacea and explore new therapeutic strategies. Methods: Transcriptome data from rosacea patients combined with immunohistochemical staining were used to investigate the activation of STAT3 in rosacea. The role of STAT3 activation in rosacea was subsequently explored by inhibiting STAT3 activation both in vivo and in vitro. The key molecules downstream of STAT3 activation were identified through data analysis and experiments. Dual-luciferase assay and ChIP-qPCR analysis were used to validate the direct binding of STAT3 to the IL-36G promoter. DARTS, in combination with experimental screening, was employed to identify effective drugs targeting STAT3 for rosacea treatment. Results: STAT3 signaling was hyperactivated in rosacea and served as a promoter of the keratinocyte-driven inflammatory response. Mechanistically, activated STAT3 directly bind to the IL-36G promoter region to amplify downstream inflammatory signals by promoting IL-36G transcription, and treatment with a neutralizing antibody (α-IL36γ) could mitigate rosacea-like inflammation. Notably, a natural plant extract (pogostone), which can interact with STAT3 directly to inhibit its activation and affect the STAT3/IL36G signaling pathway, was screened as a promising topical medication for rosacea treatment. Conclusions: Our study revealed a pivotal role for STAT3/IL36G signaling in the development of rosacea, suggesting that targeting this pathway might be a potential strategy for rosacea treatment.